Aquatic Oligochaete Biology IX 2006
DOI: 10.1007/1-4020-5368-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Sludge reduction by predatory activity of aquatic oligochaetes in wastewater treatment plants: science or fiction? A review

Abstract: Biological aerobic wastewater treatment plants (WWTPs) produce a lot of excess sludge. The costs for handling this residual product are increasing, so the search for alternative techniques to reduce the amount of sludge has to be continued. Activated sludge consists of inorganic and organic substances, bacteria, protozoa and metazoa. Due to incomplete biomass conversion, sludge consumption yields less oligochaete biomass. From a technological point of view, the application of aquatic oligochaetes to reduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 64 publications
2
27
0
1
Order By: Relevance
“…In this research, the environmental factors affecting the performance of worms were surveyed. This research confirmed the use of worms as a protein-supply source in the food for fish and domestic animals [12]. The result of a study about mass balances and processing of worm faces showed that 39% of nitrogen and 12% of phosphorus in the sludge which were digested by the worm were used in the formation of new worm biomass, which had potential for reuse [13].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…In this research, the environmental factors affecting the performance of worms were surveyed. This research confirmed the use of worms as a protein-supply source in the food for fish and domestic animals [12]. The result of a study about mass balances and processing of worm faces showed that 39% of nitrogen and 12% of phosphorus in the sludge which were digested by the worm were used in the formation of new worm biomass, which had potential for reuse [13].…”
Section: Introductionsupporting
confidence: 63%
“…The result of this research (30%) was almost equal to that (33%) of the present research in which the worm species and the treatment method were applied in the process (activated sludge) [12].…”
Section: Discussionsupporting
confidence: 48%
“…A special case of excess sludge reduction is by means of aquatic worms that naturally inhabit aerobic zones in WWTPs [11]. Several different sessile and free swimming oligochaete worm species have been investigated with a variety of reactor designs for their ability to degrade sludge (see Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, the removal of proteins from the extracellular polymeric substances (EPS) matrix, during sludge predation, could be due to the consumption of bacteria residing in the EPS. The removal of bacteria from ingested particles, which can be referred to as 'microbial stripping' [18], results in changes in microbial community of the natural sediments the worms inhabit [19]; or in case of sludge reduction, changes in the microbial community of the sludge reduction system the worms inhabit [20].…”
Section: Introductionmentioning
confidence: 99%